Activities of Gemifloxacin (SB 265805, LB20304) Compared to Those of Other Oral Antimicrobial Agents against Unusual Anaerobes - Goldstein, Ellie J. C. (American Society for Microbiology, 1999)
The activities of gemifloxacin (SB 265805, LB20304) and comparator agents were determined by an agar dilution method against 419 clinical strains of less-commonly identified species of anaerobes. Gemifloxacin was generally more active than trovafloxacin against gram-positive strains by one to two dilutions. Peptostreptococci (Peptostreptococcus asaccharolyticus, Peptostreptococcus magnus, Peptostreptococcus micros, and Peptostreptococcus prevotii) and Porphyromonas spp. (Porphyromonas asaccharolytica, Porphyromonas canoris, Porphyromonas gingivalis, and Porphyromonas macacae) were all susceptible to ≤0.25 μg of gemifloxacin per ml. The MICs of gemifloxacin at which 90% of the following strains were inhibited (MIC(90)s) were ≤2 μg/ml: Actinomyces israelii, Actinomyces odontolyticus, Clostridium innocuum, Clostridium clostridioforme, Anaerobiospirillum spp., Bacteroides tectum, Bacteroides ureolyticus, Bacteroides gracilis (now Campylobacter gracilis), Prevotella intermedia, Prevotella heparinolytica, and the Prevotella oris-buccae group. Fusobacterium naviforme and Fusobacterium necrophorum were also susceptible to ≤2 μg of gemifloxacin per ml, while Fusobacterium varium strains exhibited a bimodal pattern; the other Fusobacterium species, such as Fusobacterium ulcerans and Fusobacterium russii, as well as Veillonella spp., the Prevotella melaninogenica group, Prevotella bivia, Clostridium difficile, and Bilophila wadsworthia were relatively resistant to gemifloxacin (MIC(90)s, ≥4 μg/ml).